Serum C-Reactive Protein Levels in Hypertensive Patients in Aceh: An Ethnic-Based Study - Desiana Desiana; Cut Murzalina; Munadi Munadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Inflammation is a key factor in the pathophysiology of hypertension. One of the inflammatory biomarkers that can be used to gauge the level of systemic inflammation in hypertensive patients is C-reactive protein (CRP). This study investigated the role of CRP among hypertensive patients in Aceh according to ethnic background. This study adopted an observational analytical design. A total of 120 participants were enrolled in the study, comprising 90 hypertensive patients from three ethnic groups (Gayo, Aneuk Jamee, and Acehnese), with 30 participants in each ethnic group, and 30 normotensive individuals who served as the control group. The Kruskal-Wallis test was used to assess intergroup variations in CRP concentrations, while the Spearman’s rho correlation was used to examine the association of CRP levels among hypertensive subjects across ethnic groups in Aceh, as well as comparisons with normotensive controls. Among participants, 54% had normal CRP levels, whereas 46% had elevated levels. Mean CRP concentrations were higher in female than in males; however, this difference did not reach statistical significance (p = 0.061). Stratification by ethnic group revealed a statistically significant variation in mean CRP levels (p = 0.001), with the highest values observed among the Aneuk Jamee group. Nevertheless, no significant correlation was identified between CRP levels and the occurrence of hypertension across ethnic groups in Aceh (p > 0.05). C-reactive protein (CRP) levels varied among Aceh's ethnic groups, but there was no discernible correlation with the prevalence of hypertension. These results imply that the regulation of inflammatory processes in people with hypertension may be influenced by non-ethnic factors.